Home Infusion Therapy: Utilization Under the Medicare Part B Temporary Transitional Payment. Issue 3 (August 2022) - Hamilton, Morris; Juergens, Mary; Zheng, Qing; Campbell, Elizabeth; Plotzke, Michael
The Bipartisan Budget Act (BBA) of 2018 1 created a temporary transitional payment (TTP) through Medicare Part B, which establishes fee-for-service (FFS) payment for eligible home infusion suppliers when they furnish home infusion therapy (HIT) service visits by skilled professionals in a beneficiary's home on the day of HIT drug administration. Payment varies by 3 condition-specific payment categories. The Centers for Medicare & Medicaid Services (CMS) implemented the TTP on January 1, 2019. The TTP ended when the permanent HIT benefit began on January 1, 2021. To better understand how beneficiaries utilized this benefit during the TTP period, we examine trends in HIT services utilization between January 2019 and December 2020. Despite being new, the HIT benefit showed only a slight ramp-up phase, with a stable level of visits evolving over the remainder of 2019 and early 2020. Utilization decreased during the COVID-19 public health emergency, especially for infusion drugs related to heart failure and cancer. Additionally, relative to the geographic distribution of the Medicare FFS population, HIT service visit users are concentrated in the mid-Atlantic states. HIT service visit users are more likely to be young, white or black, and urban dwelling, compared to the general Medicare FFS beneficiaries.